The good, the bad and the Ulva: the density dependent role of macroalgal subsidies in influencing diversity and trophic structure of an estuarine community. Issue 7 (17th November 2015) - Green, Lauri; Fong, Peggy
Abstract : Worldwide, ecological subsidies enhance ecosystem productivity and therefore trophic support for greater biodiversity of taxa. While studies in terrestrial and aquatic ecosystems demonstrate that the magnitude of subsidies into ecosystems differs widely, the thresholds where subsidies may switch from exerting positive to negative effects are poorly understood. In estuaries, eutrophication promotes drift macroalgae that deposit on the benthos, cover intertidal flats for months and serve as pressed resource subsidies for benthic consumers. We hypothesized there would be a critical threshold of macroalgal biomass where ecosystem‐level effects would turn from positive to negative. We used manipulative field experiments varying macroalgal mat thickness (0.5, 1.5 and 4 cm) over eight weeks and quantified effects on macrofauna on a lagoon mudflat in California. We documented that plots with mat depths of 0.5 and 1.5 cm had higher diversity by supporting both surface feeding and burrowing detritivores. Non‐metric multidimensional scaling showed that the benthic community diverged with mat depth over the course of the experiment. After eight weeks, surface deposit feeders were associated mainly with 0.5 cm macroalgal subsidies, whereas subsurface deposit feeding capitellids were closely linked with 4 cm mats. Depth profiles of pore water sulfide concentration collected from 4 cm mats were 7622 ± 5294 μM, mean ± SE, (mean of means across depth profiles), whereas 0.5 cm treatments resulted in sulfide concentrations that were 0.25% of the 4 cm treatments. This suggests that the mechanism of negative effects for elevated macroalgal subsidies was development of anoxic conditions promoting sulfide accumulation. Thus, our study was the first to find a critical threshold, or ecological tipping point, beyond which the effects of anthropogenically enhanced subsidies to estuarine mudflat communities switched from positive to negative and to describe the mechanism by which elevated subsides altered the abiotic environment and likely reduced ecosystem functioning.